Digital technology and justice : justice apps - Sourdin, Tania; Meredith, Jacqueline; Li, Bin (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Justice apps - mobile and web-based programs that can assist individuals with legal tasks - are being produced, improved, and accessed at an unprecedented rate. These technologies have the potential to reshape the justice system, improve access to justice, and demystify legal institutions. Using artificial intelligence techniques, apps can even facilitate the resolution of common legal disputes. However, these opportunities must be assessed in light of the many challenges associated with app usage in the justice sector. These include the digital divide and other accessibility issues, the ethical challenges raised by the dehumanisation of legal processes, and various privacy, security, and confidentiality risks. Surveying the landscape of this emergent industry, this book explores the objectives, opportunities, and challenges presented by apps across all areas of the justice sector. Detailed consideration is also given to the use of justice apps in specific legal contexts, including the family law and criminal law sectors. The first book to engage with justice apps, this book will appeal to a wide range of legal scholars, students, practitioners and policy-makers"--
Digital technology use in the justice sector -- Justice apps -- Objectives and opportunities -- Justice apps in context -- Issues with justice apps -- Future options.
"Routledge Focus" -- taken from front cover.
OCLC-licensed vendor bibliographic record.
Keywords: Justice, Administration of -- Data processing; Information storage and retrieval systems -- Law; COMPUTERS / Artificial Intelligence; COMPUTERS / Internet / Application Development; COMPUTERS / Social Aspects / General